The influence of the dispersed oxides on the interface energy of the microcrystaliine cellulose in water suspension - Shulga, O. V.; Kerchhoff, J.; Turov, V. V. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2001)
The characteristics of water bounded layers in the hydrated powders and water suspensions of microcrystalline cellulose and thought containing SiO2 or TiO2 particles were investigated by 1H NMR method. It is found that the concentration of strong bounded water and the γs value are in a strong dependence to the concentration of cellulose in suspension. Probably, it is dictated by strong interaction between cellulose particles. At the very high concentration of suspension concentration of water inside the cellulose filament decreases in more than 3 time and (γs) value decreases from 9 to 31 J/g which is due to effect of surface forces. In the presence of dispersed particles of oxides, the concentration of bound water and γs value in average are decrease, aseptically in the case of suspensions with TiO2 particles.